Policies from Evidence that Risk Starvation Causes Dementias and Depressions and May Contribute to a Range of Other Brain Morbidities - Robin Pope (University of Bonn, Bonn Graduate School of Economics (BGSE), 2009)
In rich countries, the population percentage under drug therapy for depressions is rising rapidly decade by decade for children, adolescent and young adults with no evidence of any long term success for this chronic ailment. There is also in rich countries relative to most poor ones, for each age cohort, a dramatically higher incidence of dementias. This paper takes a fresh look at these evidences of happiness problems that are so much more prevalent in rich than poor countries...
Keywords: 330; brain morbidities; brain exercise; decision making; dementia; depression; environmental factors; risk processing; risk starvation; whiffs of danger; frequent; tiny; varied chances and challenges; damaging social security welfare; socio-economic changes; societal interactions; societal contributions; pharmaceutical advertising; pharmaceutical sponsorship; Psychische Störung; Risikopräferenz; Emotion; Sozialer Wandel; Soziale Beziehungen; Gesundheitsvorsorge; Pharmazeutische Industrie; Interessenpolitik